I have an integral surface $z = z(x, y)$.

Writing this integral surface in implicit form, we get

$$F(x, y, z) = z(x, y) - z = 0$$

I am then told that the gradient vector $\nabla F = (z_x, z_y, -1)$ is normal to the integral surface $F(x, y, z) = 0$.

First of all, how was this calculated? I understand how the gradient is calculated, but I don't understand how it was calculated in this case?

And lastly, where did the $-1$ come from and why? Couldn't they also have had $\nabla F = (z_x, z_y, 1)$, where this would just be the normal vector in the other direction? Why and how did they pick the $-1$ direction instead?

I apologise. My vector calculus understanding is not particularly strong, and I strive to improve it.

Thank you for any help.


maybe its helpful to give the surface equation a different symbol $$ S = \{ (x,y,z) : z=Z(x,y) \}$$ then with $F(x,y,z):= Z(x,y) - z$,

$$∇ F (x,y,z) = \begin{pmatrix}\partial_x( Z(x,y) - z)\\\partial_y( Z(x,y) - z)\\\partial_z( Z(x,y) - z)\end{pmatrix}= \begin{pmatrix}\partial_x Z(x,y)\\\partial_yZ(x,y)\\\ - 1\end{pmatrix}$$ The $-1$ came from the definition of $F$. If you forced $+1$ instead of $-1$ you would be talking about $Z(x,y) + z$ which is not related to $S = \{F = 0 \}$.

If you take any curve $\mathbf x=\mathbf x(t)$ such that $\mathbf x(t) ∈ S$ for every $t$, then

$$ F(\mathbf x(t)) = 0 $$ taking derivatives, $$∇ F(\mathbf x)· \mathbf x' = 0$$ but the collection of all such $\mathbf x'$s as you consider different curves $\mathbf x$ form the tangent vectors at each point of $S$. Therefore, $∇ F$ is perpendicular to all tangent vectors of $S$ at that point. In dimension 3, there are 2 linearly independent tangent vectors and you get a unique normal vector (up to scaling and sign).

  • $\begingroup$ Ahh, you used different variables $z$ and $Z$, so it makes sense now. But the author used $z$ for both, but treated $z(x, y)$ as a function of 2 variables and $z$ as a constant in the same expression, which makes it confusing, because the author also just said that $z = z(x, y)$. Seems paradoxical? As if $z$ is both a function of $x$ and $y$ and a constant! $\endgroup$ – Wyuw Jul 29 '18 at 10:23
  • 1
    $\begingroup$ @Wyuw yes well, this is the way of things unfortunately and you may need to get used to it $\endgroup$ – Calvin Khor Jul 29 '18 at 10:24
  • $\begingroup$ Yes, thank you for your help! $\endgroup$ – Wyuw Jul 29 '18 at 10:25
  • 1
    $\begingroup$ @Wyuw You're welcome. good luck :) $\endgroup$ – Calvin Khor Jul 29 '18 at 10:26

Let us start with an example.

$$ z=x^2+y^2$$ $$ F(x,y,z)=x^2+y^2-z$$ $$\nabla F = (z_x, z_y, -1)=< 2x,2y,-1>$$

If a point is given, for example $P(1,2,5)$ Then at that point you have two normal vector to the surface.

Upward normal $$< -2x,-2y,1> = <-2,-4,1>$$ Downward normal $$< 2x,2y,-1> = <2,4,-1>$$

  • $\begingroup$ Ahh, thank you for this. I understand your example, but in the case of $F(x, y, z) = z(x, y) - z = 0$, we have that $z = z(x, y)$, so it is not a constant? So how can we say that $\nabla F = (z_x, z_y, -1)$? That is why I am confused about where the $-1$ comes from? $z$ is still a function of $x$ and $y$, no? But it is being treated as a constant here, and then it is treated as a variable of $x$ and $y$ in the same expression when they calculate $z_x$ and $z_y$! $\endgroup$ – Wyuw Jul 29 '18 at 10:19
  • 1
    $\begingroup$ $z=z(x,y) $is the explicit equation of the surface surface and $F(x,y,z)=z(x,y,)-z =0 $ is the equation of the same surface implicitly. The vector of partial derivatives of $F(x,y,z)$ gets its $-1$ from the $-z$ in $z(x,y,)-z$ $\endgroup$ – Mohammad Riazi-Kermani Jul 29 '18 at 10:27
  • $\begingroup$ I understand now. Thank you $\endgroup$ – Wyuw Jul 29 '18 at 10:31
  • 1
    $\begingroup$ Thanks for your attention. $\endgroup$ – Mohammad Riazi-Kermani Jul 29 '18 at 10:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.